Cine por la paz del mundo : Latin America congratulates the International Film Festival - Pol, Santiago; Oriach, Frank (Venezuela. Ministerio de Relaciones Exteriores. Relaciones Culturales)
Photograph of dove on a nest made of filmstrips Poster by the Venezuelan government, congratulating the International Film Festival, Leipzig, 19-26 November, 1982 PO-0240